The Implementation of TikTok Aplication to Increase The Students Speaking Skill - Basri, Megawati; Wahyuni, Rina (MARAS : Jurnal Penelitian Multidisiplin, 2024)
English is the international language that should be understand by many people in this world. Nevertheless, some students felt difficult to learn English. The problem is grammar error, lack of vocabulary, and lack of self-confident in speaking English. It challenges the teacher to facilitate the students to learn. This digital era push the teacher to connect the digital and the learning strategy. For that reasons the researcher try to apply the TikTok application in the learning process. Thus, the aim of this research is to know whether TikTok application can improve the students speaking skill or not? This research conducted in MTs Negeri 2 Murotai Timur. The samples in these research students the second grade of MTs Negeri 2 Morotai Timur with the total of students are 30 students. The researcher uses a pre-experimental that focuses on using one group as a pre-test and post-test. The result of this research showed that the pre-test were 5,30 and after implemented the of using TikTok application, the mean of the post-test were 7,27. It means that the implementation of TikTok application can improve the students speaking skill.